Negras e Negros de última hora: Uma análise das estratégias de afroconveniência dos estudantes beneficiários da politica de ação afirmativa denunciados por fraudes na Universidade Federal do Maranhão - MACEDO, Rodvania Frazão (2023)
This work is linked to the research group “Politics, Educational Management and Human Training” which makes up the research line “History, Educational Policies, Work and Human Training” of the Postgraduate Program in Education-PPGE at the Federal University of Maranhão- UFMA. Last minute blacks and blacks is an analysis of the self-declarations of quota students accused of fraud at UFMA, which seeks to understand the strategies that were used to access the places reserved for racial quotas, established by Law 12,711/2012. To this end, during the course of the study, reflections are developed on the more general conceptual and historical aspects of the right to education, the struggles of the black population and affirmative action policies. The locus of the research is the medical course on the campuses of Imperatriz, Pinheiro and São Luís, from 2013 to 2019, totaling 31 people reported. With a qualitative approach, bibliographic and documentary research was adopted, as well as the content analysis technique proposed by Bardin (1977). For theoretical-methodological foundation, we turned to authors who work with affirmative actions such as Feres, Campos and Daflon (2020), Gomes (2003), Guimaraes (1998), Santos (2003, 2005, 2014 and 2021), and with the questions racial ethnicities such as Munanga (2019), Nilma Gomes (2017), Almeida (2019), Vaz (2018) and Schucman (2023). To understand the affirmative action policy within the scope of UFMA, we refer to its institutionalization in the period before and after Law 12,711/12, based on the notices and resolutions from the periods from 2006 to 2009, Institutional Development Plan-PDI for the five-year period 2012-2016, 2017-2021 and 2022-2026 and the racial self-declaration instrument. The results found indicate that last-minute black men and women are in reality real beneficiaries of whiteness and use Afro-convenience strategies to neutralize the demands, struggles and rights of the black population in relation to access to higher education reserved under Law 12,711 /12.